(untitled) (Global Journal of Human-Social Science, 2016)
We investigated the effects of stigma on uptake of Antiretroviral Therapy among women attending Prevention of Mother to Child Transmission clinics in Kenya. This was a cross sectional descriptive study where all the 280 women who attended 6 health facilities in Rachuonyo North Sub County during the study period were sampled. Data were collected using questionnaires and Key-informant guide for PMTCT Health Officers in charge of the clinics. Data analyzed using descriptive statistics and using content analysis. The study established that enacted stigma influenced ART uptake by causing160 (65%) to stop taking anti-retroviral drugs, anticipated stigma influenced ART uptake by causing 177(63%) women to stop taking antiretroviral, consequently perceived community stigma influenced ART uptake by causing 168(60%) respondents to stop taking antiretroviral drugs and self-stigma led to stoppage of antiretroviral drugs among 184(66%) women. The study highlighted the need to address stigma to improve ART uptakein PMTCT settings.